ANALISIS PENERIMAAN APLIKASI GABLIND MENGGUNAKAN METODE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY TERHADAP PERILAKU PENGGUNA - Monalisa Fatmawati Sarifah; Ema Utami; Asro Nasiri (Informasi Interaktif, 2019)
Gablind is an Android-based application which used as assisting tool for enhancing mobility of visually impaired person. But, in it’s actual use, Gablind have not get positive feedback from user. Acceptance factor become one of big factor for succession of an application. One of method that can be use to measure user acceptance is Unified Theory Of Acceptance And Use Of Technology (UTAUT. This research proved performance expectancy, effort expectancy, social influence effect to behavior intention variable and facilitating condition effect to use behavior with help of gender, age, experience, voluntariness of use moderators. Data retrieved from thirty sample that consist from visually impaired person from YAKETUNIS Institution Yogyakarta. Data processing analysed using SPSS. Research result showed there are positive and negative effects between variable context. Performance expectancy proved does not have no effect toward behavior intention. While effort expectancy and social influence have positive effect and significantly affect behavior intention. Facilitating condition and behavior intention also have positive effect and significantly affect use behavior.   Keywords: gablind, acceptance, UTAUT.